1998
DOI: 10.2307/3579649
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Biological Interface Dose Effects in Tissue due to X-Ray-Induced Release of Secondary Radiation from Metallic Gold Surfaces

Abstract: Dose enhancement up to more than a factor of 100 was found in an environment of tissue-equivalent polymethylmethacrylate (PMMA) close to the surface of a thin metallic gold foil. The enhancement factors were determined for heavily filtered X rays (40 to 120 kV tube potential) under backscatter conditions, using thin-film radiation detectors with sub-micrometer resolution. The secondary electrons were found to range up to some 10 microm in tissue-equivalent material. Correspondingly, enhanced biological effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 22 publications
4
73
0
Order By: Relevance
“…Using physical dosimetry, Regulla et al [65] demonstrated massive DEFs of 55-114 when detectors were placed next to gold foil encased in polymethylmethacrylate (PMMA) and irradiated with mean X-ray energies of 33-100 kV. With 80 kV X-rays, the secondary radiation decreased exponentially with the distance from the gold foil and was negligible at 30 mm.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Using physical dosimetry, Regulla et al [65] demonstrated massive DEFs of 55-114 when detectors were placed next to gold foil encased in polymethylmethacrylate (PMMA) and irradiated with mean X-ray energies of 33-100 kV. With 80 kV X-rays, the secondary radiation decreased exponentially with the distance from the gold foil and was negligible at 30 mm.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…[12][13][14] A tissue modeling study using gold foil reported a dose enhancement factor of 50 due to the production of secondary electrons generated from low-energy photon irradiation. 15 Subsequent progression to produce smaller particles, thereby increasing the gold surface area to volume ratio, resulted in the production of gold particles in the nanometer range. Hainfeld et al 6 detailed the first study using 1.9 nm gold nanoparticles as radiosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical simulations have shown gold (Z = 79) compounds as ideal radiation enhancing agents [15][16][17]. Several experimental attempts have been made to exploit the radiation enhancing properties of gold for therapeutic benefit using gold foils [18,19] and microparticles [20].…”
Section: Introductionmentioning
confidence: 99%